Impaired atrial mitochondrial calcium handling in patients with atrial fibrillation - Pronto, Julius Ryan D.; Mason, Fleur E.; Rog-Zielinska, Eva A.; Fakuade, Funsho E.; Bülow, Donata; Tóth, Marcell; Machwart, Khaled; Brandes, Paulina; Wiedmann, Felix Tobias; Kohlhaas, Michael; Nickel, Alexander; Wolf, Matthias; et al. (Circulation research, 2025)
BACKGROUND: - Mitochondrial calcium (Ca2+) is a key regulator of cardiac energetics by stimulating the tricarboxylic acid cycle during elevated workload. Atrial fibrillation (AF) is associated with a reduction in cytosolic Ca2+ transient amplitude, but its effect on mitochondrial Ca2+ handling and cellular redox state has not been explored. - METHODS: - Cardiac myocytes isolated from patient-derived right atrial biopsies were subjected to workload transitions using patch-clamp stimulation and β-adrenergic stimulation (isoproterenol). In conjunction, nicotinamide adenine dinucleotide (phosphate)/flavin adenine dinucleotide (NAD[P]H/FAD) autofluorescence, cytosolic and mitochondrial [Ca2+] were monitored using epifluorescence microscopy. Sarcoplasmic reticulum and mitochondria were imaged using electron microscopy and tomography and stimulated emission depletion microscopy. The effects of the mitochondrial Ca2+ uptake enhancer ezetimibe on proarrhythmic activity in atrial myocytes and on AF burden in patients were investigated. - RESULTS: - Mitochondrial Ca2+ accumulation during increased workload was blunted in AF, and was associated with impaired regeneration of nicotinamide adenine dinucleotide and flavin adenine dinucleotide. Nanoscale imaging revealed spatial disorganization of sarcoplasmic reticulum and mitochondria, associated with microtubule destabilization. This was confirmed in human induced pluripotent stem cell-derived cardiac myocytes, where treatment with the microtubule destabilizer nocodazole displaced mitochondria and increased proarrhythmic Ca2+ sparks, which were rescued by MitoTEMPO. Ezetimibe also reduced the occurrence of arrhythmogenic Ca2+ release events both in AF myocytes and nocodazole-treated human induced pluripotent stem cell-derived cardiac myocytes. Retrospective patient analysis also revealed a reduced AF burden in patients on ezetimibe treatment. - CONCLUSIONS: - Mitochondrial Ca2+ uptake and accumulation are impaired in atrial myocytes from patients with AF. The disturbed spatial association between sarcoplasmic reticulum and mitochondria driven by destabilized microtubules may underlie impaired Ca2+ transfer in AF. Enhancing mitochondrial Ca2+ uptake potentially protects against arrhythmogenic events.